2008
DOI: 10.1161/circulationaha.107.792747
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Proteomic Profile of Differentially Regulated Proteins in Right Atrial Appendage Before and After Cardiac Surgery Using Cardioplegia and Cardiopulmonary Bypass

Abstract: Background-Although highly protective, cardiac surgery using cardioplegia and cardiopulmonary bypass (CP/CPB) subjects myocardium to hypothermic reversible ischemic injury that can impair cardiac function which results in a greatly enhanced risk of mortality. Acute changes in myocardial contractile activity are likely regulated via protein modifications. We performed the following study to determine changes in the protein profile of human myocardium following CP/CPB. Methods and Results-Right atrial appendage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…The importance of the mitochondrion and the mitochondrial proteome have been previously demonstrated; our data agree with the proteomic data of others who have shown changes in energy metabolism pathways following ischemia and reperfusion (6). In particular our data would agree with that of White et al (44) who have shown that ischemia-reperfusion in the New Zealand White rabbit results in changes in the proteome and includes changes in contractile fiber and energy production, similar to our findings.…”
Section: Discussionsupporting
confidence: 93%
“…The importance of the mitochondrion and the mitochondrial proteome have been previously demonstrated; our data agree with the proteomic data of others who have shown changes in energy metabolism pathways following ischemia and reperfusion (6). In particular our data would agree with that of White et al (44) who have shown that ischemia-reperfusion in the New Zealand White rabbit results in changes in the proteome and includes changes in contractile fiber and energy production, similar to our findings.…”
Section: Discussionsupporting
confidence: 93%
“…SDS-PAGE and immunoblotting were performed using standard methodology as previously described (6). Antibodies for immunoblotting and confocal microscopy were as follows: phospho-specific and total HSP27, total HSP25, and cryAB antibodies were obtained from Stressgen (Vancouver, BC); phosphoand total p38 MAPK were obtained from Cell Signaling (Danvers, MA), and anti-MLC-2v was obtained from Synaptic Systems (Göt-tingen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…6,7 Several groups have shown that PCT increased both the amount and number of extracted proteins from cells. [8][9][10][11] The utility of PCT for extracting DNA from lowtemplate forensic samples, 12,13 including hair, 14,15 bone fragments, 16 skin and blood stains, 15 sexual assault samples, 17 and fecal matter, 18 has also received some attention, due to the foreseeable advantages of an automated approach for reducing casework backlogs and potentially improving DNA recovery. In addition to reducing backlogs, using PCT may decrease the risk of cross-contamination and sample mix-ups, especially in cases where hairs submitted for DNA analysis arrive at the laboratory on an item of clothing.…”
Section: Introductionmentioning
confidence: 99%